A comparative case study of the implementation of standardised tools in healthcare: the active role everyday technologies play in quality improvement - Overton, Charlotte (2020)
The implementation of evidence-based medicine frequently hinges on the introduction of technologies and tools within established social practices, and so often requires behavioural or cultural change at the clinical frontline. This research explored the implementation of an evidence-based intervention, in the form of a standardised tool, in the English National Health Service (NHS). In this context, local implementation of an evidence-based intervention is under the influence of external forces such as: NHS targets and financial incentives; the political landscape; and the public and media.